Delivering urban mobility solutions - Finer, Mark; Šesták, Daniel (Univerzita Pardubice, 2010)
With sixty percent of the population in Europe living in urban areas and three quarters of all trips undertaken by car, the question of how to enhance mobility while at the same time reducing congestion, accidents and pollution is a common challenge to all major cities in Europe. Mobility in urban areas is an important factor which affects economic growth, employment and facilitates sustainable development. Traditional 'predict and provide' approaches to transport planning are no longer sufficient to meet future transport needs in a sustainable way and today 'predict and manage' approaches are required to deliver sustainable urban mobility solutions. In September 2007 the European Commission published a new Green Paper "Towards a new culture for urban mobility" reiterating the importance of achieving free-flowing and greener towns and cities, smarter urban mobility and urban transport which is accessible, safe and secure. The paper will explore current thinking and approaches for delivering improved urban mobility in urban areas, drawing on examples in the UK and experience in Ceske Budejovice where a new comprehensive integrated transport plan is being developed setting out how sustainable transport can be accommodated for the next 20 years.
Keywords: urban mobility; sustainable; accessibility; integration